Taxation in six concepts : a students guide - Alstott, Anne, 1963- (Wolters Kluwer, 2015)
"In this book, I introduce the six concepts and use them to unpack leading cases and real-world transactions. The six are: valuation, net income, realization, tax deferral, substance over form, and income-shifting"--Page iii
Terminologický slovník
Keywords: daně z příjmů -- Spojené státy americké; income tax -- United States; učebnice vysokých škol; textbooks (higher)